Corn peptide enhances exercise performance and prevents myocardial damage of mice caused by overtraining through activating autophagy. (October 2022) - Wu, Qiuyue; Tao, Jingjing; Wu, Liangwen; Wei, Wei; Zhang, Xiping; Zhang, Zhao; Zhang, Xuejun; Jiang, Xia; Chen, Ning
Graphical abstract: Corn peptide combined regular swimming intervention synergistically enhanced exercise performance of the mice through delaying exercise fatigue and protecting myocardial injury caused by exhaustive exercise or overloaded exercise training. Highlights: Corn peptide enhances exercise performance. Corn peptide prevents myocardial damage of mice caused by overtraining through activating autophagy. Corn peptide synergistically promotes exercise performance from regular exercise training. Abstract: To explore the effect of corn peptide on enhancing exercise performance and preventing overtraining-induced myocardial injury, 40 male mice were divided into normal control, swimming training control, swimming training with low, medium, and high-dose corn peptide groups for 8-week interventions. After interventions, exhaustive swimming time and blood lactate were determined to evaluate exercise performance. Creatine kinase (CK) and CK-MB levels were determined by ELISA. The proteins associated with autophagy and apoptosis in myocardial tissue were evaluated by Western blot. Results indicated that corn peptide could effectively prolong exhaustive swimming time, and accelerate blood lactate elimination, suggesting its enhancing exercise performance and alleviating exercise fatigue. Meanwhile, it could also reduce serum CK and CK-MB levels, up-regulate Atg7 and Beclin1, increase LC3-II/LC3-I ratio, and down-regulate p62 and Bax. Therefore, corn peptide cooperated with regular swimming training can enhance exercise performance and execute overtraining-induced myocardial protection through activating autophagy and inhibiting apoptosis.